Two new species of the lichen genus Strangospora (Lecanoromycetes: Strangosporaceae) from India - Kumar, Vishal; Ingle, Komal Kumar; Upreti, Dalip Kumar; Nayaka, Sanjeeva; Sharma, Yash Pal (Phytotaxa, 2025)
Strangospora himalayana and S. submoriformis are described as new species from India. Both the species have thin, greyish thallus, poorly developed exciple, K–, N– epithecium and simple, hyaline, globose ascospores. Further, Strangospora himalayana has a minutely arachnoid thallus, hyaline to pale brown epithecium and ascospores of size 1–2.5 μm, while S. submoriformis has a granular thallus, olivaceous epithecium and ascospores measuring 2.5–3 μm. This is the first report of the genus Strangospora from India, collected from north-western Himalaya. A detailed description, illustrations, habitat and ecology, comparisons with similar members along with a world key to all accepted species of Strangospora are provided.